2022
DOI: 10.1007/s00330-022-08592-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning reconstruction improves radiomics feature stability and discriminative power in abdominal CT imaging: a phantom study

Abstract: Objectives To compare image quality of deep learning reconstruction (AiCE) for radiomics feature extraction with filtered back projection (FBP), hybrid iterative reconstruction (AIDR 3D), and model-based iterative reconstruction (FIRST). Methods Effects of image reconstruction on radiomics features were investigated using a phantom that realistically mimicked a 65-year-old patient’s abdomen with hepatic metastases. The phantom was scanned at 18 doses from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Our study showed that most radiomic features obtained from LV myocardium differ depending on the reconstruction methods and are presumably affected by the reconstruction method. This result is in line with a previous study showing that applying DLR yielded superior feature consistency, discriminative power and repeatability to IR, and FBP for radiomic features on abdominal CT 30 . DLR uses a deep neural network to enhance image quality by removing noise from signal without changing the noise texture itself and is thought to produce adequate images for feature extraction and diagnostic modelling.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that most radiomic features obtained from LV myocardium differ depending on the reconstruction methods and are presumably affected by the reconstruction method. This result is in line with a previous study showing that applying DLR yielded superior feature consistency, discriminative power and repeatability to IR, and FBP for radiomic features on abdominal CT 30 . DLR uses a deep neural network to enhance image quality by removing noise from signal without changing the noise texture itself and is thought to produce adequate images for feature extraction and diagnostic modelling.…”
Section: Discussionsupporting
confidence: 92%
“…The IR algorithm tended to produce CT images with a more “plastic-looking” texture than FBP reconstructions, so the effects of IR on quantitative radiomic features make sense 29 . Although DLR aims to produce a more natural texture similar to FBP reconstruction, few studies to date have investigated the effects of DLR on quantitative radiomic features 30 . Our study showed that most radiomic features obtained from LV myocardium differ depending on the reconstruction methods and are presumably affected by the reconstruction method.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, standardization initiatives such as the image biomarker standardization initiative 40 can facilitate increasing the comparability of quantitative imaging data as it was shown that extraction algorithms can have an influence on radiomics features. Deep learning-based reconstruction models can be used 41 to standardize images and increase feature stability. Now, the implementation of PCCT with its intrinsic capability of spectral reconstructions may be regarded as an additional tool to address the issue of feature stability, which remains a relevant impediment to the clinical application of radiomics, by utilization of energy-specific reconstruction techniques.…”
Section: Discussionmentioning
confidence: 99%
“…A widely proposed solution to further increase the stability of quantitative imaging approaches is the application of deep learning reconstruction methods to imaging data [ 33 ]. While this approach has shown promising results in the prediction of known phenotypes [ 34 ], it has some limitations in an unsupervised approach, because a ground truth for training cannot be defined easily.…”
Section: Discussionmentioning
confidence: 99%